Crack detection using image processing techniques for radiographic inspection of aircraft wing spar - Wong, B Stephen; Wang, Xin; Koh, Chen Ming; Tui, Chen Guan; Tan, Chingseong; Xu, Jian (2011)
Radiographic inspection is one of the most important non-destructive inspection methods for aircraft wing spar inspection. Traditionally, radiographic inspection is time and manpower consuming. In addition, human inspection of cracks and damage based on film radiography is very subjective, inconsistent and sometimes biased. To improve the speed and efficiency of radiographic inspection, digital X-ray systems are gaining popularity over traditional film-based X-ray. Digital radiography has emerged as a leading technology for aircraft inspection. Therefore, it is desirable to develop a computer-aided system to assist in the interpretation of digital radiographic images to increase the objectivity, accuracy and efficiency of radiographic interpretation. In this paper, a crack detection algorithm using region of interest (ROI) minimisation, thresholding and edge detection techniques is developed for radiographic inspection of an aircraft wing spar.